4G TECHNOLOGY (International Journal of Engineering and Computer Science, 2013)
The approaching 4G (fourth   generation) mobile communication systems are projected  to solve still-remaining problems of 3G (third  generation)  systems  and  to  provide  a  wide  variety  of  new  services,  from  high-quality voice to high-definition video to high-data-rate wireless channels.The term 4G is usedbroadly to include several  types of broadband wireless access communication systems, not only cellular telephone systems. One of the terms used to describe 4G is MAGIC—Mobile multimedia, anytime anywhere, Global mobility support, integrated wireless solution, and customized personal service. As a promise for the future, 4G systems,  that is, cellular broadband wireless access systems have been attracting much interest in the mobile communication arena.The 4G  systems  not only will support the next generation of mobile service, but also will support the fixed wireless networks.This paper presents an overall vision  of the 4G features, framework, and integration  of mobile communication. The features of 4G systems might be summarized  with  one word—integration. The 4G systems are about seamlessly  integrating  terminals,  networks, and  applications  to  satisfy  increasing  user demands. The continuous expansion of mobile communication and wireless networks shows evidence of exceptional growth in the areas of mobile  subscriber,  wireless  network  access, mobile services, and applications. .